Self-compassion education for older adults' mental health and wellbeing: a mixed methods systematic review. - Othman, Shwikar; Steen, Mary; Abdelnasser, Nadia (2025)
OBJECTIVES: To assess and explore the influence of self-compassion education for older adults' mental health and wellbeing; and identify facilitators and challenges that may impact providing self-compassion education for older adults' mental health and wellbeing. METHOD: A mixed methods systematic review was conducted following Joanna Briggs Institute (JBI) methodology. A three-stage search approach was undertaken that included six electronic databases: Medline, Embase, PsycINFO, Emcare, Ovid Nursing, Cochrane Library, and grey literature. Quality assessment was conducted via mixed methods appraisal tools. Quantitative data were synthesised into a narrative summary of the characteristics and findings of the influence of self-compassion education for older adults. For the qualitative data, a thematic synthesis was conducted. RESULTS: Eleven studies met the inclusion criteria. Overall, the included studies reported that self-compassion education for older adults was associated with improved psychological well-being, and higher levels of self-compassion, kindness towards oneself and others, and mindfulness. In addition, participants reported reduced distress, anxiety, and avoidance of negative experiences. CONCLUSION: The findings provide evidence to guide further research on developing, designing, facilitating, and evaluating self-compassion education programs and workshops for older adults. PROSPERO REGISTRATION: This systematic review is registered at the International Prospective Register of Systematic Reviews: PROSPERO 2022 CRD42022310630.